Pelaksanaan Layanan Kenotariatan Berbasis Digital dalam Meningkatkan Efektivitas Pelayanan Hukum (Studi pada Kantor Notaris Darji Saputra, S.H., M.KN) - Resi Atna Sari Siregar; Hasan Basri; Nadiatul Asima; Nur Azizah Nasution; Elma Robiatul Adawiyah; Annisa Putri Rangkuti; Lenni Misriani Lubis; Asmin Hamid Nst; Ismail Nasution (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The development of information technology has driven transformation in various public service sectors, including the notary sector. Digitizing notary services is a strategic effort to improve the effectiveness, efficiency, and quality of legal services to the public. This study aims to analyze the implementation of digital-based notary services in improving the effectiveness of legal services at the Notary Office of Darji Saputra, S.H., M.Kn. The research method used is empirical legal research with a qualitative approach. Data were obtained through observations during internships, interviews with notaries and office staff, and a documentary study of the implemented digital-based service procedures. The results indicate that the implementation of digitalization in deed administration, electronic filing, communication with clients, and the use of online legal entity administration systems can improve time efficiency, data accuracy, and service transparency. However, obstacles remain, such as limited technical regulations and the need to improve digital literacy for some members of the public. Thus, digital-based notary services have been proven to contribute to improving the effectiveness of legal services, but still require regulatory strengthening and human resource readiness.